The Effect of Inquiry Learning Strategy and Learning Motivation on Mathematics Learning Outcomes of Students of Class VIII SMP Negeri 1 Parapat 2022/2023 - Rajainal Saragih; Arif Yuandana Sinaga (PT Inovasi Pratama Internasional, 2022)
The achievement of educational goals based on Law no. 20 of 2003 requires teachers to be able to choose appropriate learning methods, strategies, models and media for students so that learning becomes active and effective and can increase learning motivation. Inquiry and expository learning strategies have different foundations, especially in learning Mathematics. The research will be carried out in early August for the 2022/2023 academic year for seventh grade students at SMP Negeri 1 Prapat . The research sample is the students of class VIII-1 being the experimental class and VIII-5 being the control class. Research instruments in the form of tests and non-tests. The results showed that 1) there are differences in learning outcomes of mathematics in students who are taught with inquiry learning strategies and expository learning strategies. This is evidence that learning strategies do have an influence on learning outcomes in Mathematics. 2) There are differences in mathematics learning outcomes for students who have high and low learning motivation. This is evidence that learning motivation has an influence in learning Mathematics. 3) There is an interaction between learning strategies and learning motivation on mathematics learning outcomes.